Early Transcriptome Response of Lactococcus lactis to Environmental Stresses Reveals Differentially Expressed Small Regulatory RNAs and tRNAs - van der Meulen, Sjoerd B.; de Jong, Anne; Kok, Jan (Frontiers in Microbiology, 2017)
Bacteria can deploy various mechanisms to combat environmental stresses. Many genes have previously been identified in Lactococcus lactis that are involved in sensing the stressors and those that are involved in regulating and mounting a defense against the stressful conditions. However, the expression of small regulatory RNAs (sRNAs) during industrially relevant stress conditions has not been assessed yet in L. lactis, while sRNAs have been shown to be involved in many stress responses in other bacteria. We have previously reported the presence of hundreds of putative regulatory RNAs in L. lactis, and have used high-throughput RNA sequencing (RNA-seq) in this study to assess their expression under six different stress conditions. The uniformly designed experimental set-up enabled a highly reliable comparison between the different stress responses and revealed that many sRNAs are differentially expressed under the conditions applied. The primary stress responses of L. lactis NCDO712 was benchmarked to earlier work and, for the first time, the differential expression was assessed of transfer RNAs (tRNAs) and the genes from the six recently sequenced plasmids of NCDO712. Although we only applied stresses for 5 min, the majority of the well-known specific stress-induced genes are already differentially expressed. We find that most tRNAs decrease after all stresses applied, except for a small number, which are increased upon cold stress. Starvation was shown to induce the highest differential response, both in terms of number and expression level of genes. Our data pinpoints many novel stress-related uncharacterized genes and sRNAs, which calls for further assessment of their molecular and cellular function. These insights furthermore could impact the way parameters are designed for bacterial culture production and milk fermentation, as we find that very short stress conditions already greatly alter gene expression.